The role of digital applications in building digital reputation - مريم نباش; أمال بدرين (International Journal of Social Communication, 2025)
In today's business landscape, regardless of their size and objectives, organizations cannot afford to overlook the importance of digital tools and mechanisms in reputation management and image building. Building a digital reputation relies on a set of strategies to establish a digital presence amidst fierce competition, with the goal of engaging and communicating with their audience. One effective mechanism for building a digital reputation is implementing a digital content creation process. The article employed a descriptive-analytical methodology to examine this subject in a scholarly manner. It delved into the intricacies of the steps and tools involved in crafting digital content, offering comprehensive explanations. The article yielded several noteworthy conclusions, among them the significance of accurately analyzing the target audience by understanding their needs and interests. It emphasized the creation of digital content that is both innovative and compelling, while also providing value.